Sars-Cov-2 in children - insights and conclusions from the mandatory reporting data in Frankfurt am Main, Germany, March-July 2020 - Heudorf, Ursel; Steul, Katrin; Gottschalk, René (German Medical Science GMS Publishing House, 2020)
Introduction: From the beginning of the corona pandemic until August 19, 2020, more than 21,989,366 cases have been reported worldwide - 228,495 in Germany alone, including 12,648 children aged 0-14. In many countries, the proportion of infected children in the total population is comparatively low; in addition, children often have no or milder symptoms and are less likely to transmit the pathogen to adults than the other way round. Based on the registration data in Frankfurt am Main, Germany, the symptoms of children in comparison with adults and the likely routes of transmission are presented below. Materials and methods: The documentation of the mandatory reports includes personal data (name, date of birth, gender, place of residence), disease characteristics (date of report, date of onset of the disease, symptoms), possible contact persons (family, others) and i.a. possible activity or care in children's community facilities. All reports were viewed, especially with regard to likely transmission routes.Results: From March 1 to July 31, 2020, 1,977 infected people were reported, including 138 children between the ages of 0 and 14 years. Children had fewer and milder symptoms than adults. None of the children experienced severe respiratory symptoms or the need for ventilation. 62% of the children had no symptoms at all (19% adults), 5% of the children were hospitalized (24% adults), and none of the children died (3.8% adults).After excluding a cluster of 34 children from refugee accommodations and 14 children from a parish, 78% of the remaining 90 children had been infected by an adult within the family, and only 4% were likely to have a reverse transmission route. In 5.5% of cases, transmission in a community facility was likely.Discussion: The results of the registration data from Frankfurt am Main, Germany confirm the results published in other countries: Children are less likely to become infected, and if infected, their symptoms are less severe than in adults, and they are apparently not the main drivers of virus transmission. Therefore, scientific medical associations strongly recommend reopening schools.